Plasma Free Homocysteine Levels in Children with Idiopathic Nephrotic Syndrome - Arumugam, Venkatesh (Indian J Nephrol, 2019)
Altered metabolism of homocysteine in children with idiopathic nephrotic syndrome leads to raised plasma-free homocysteine levels. Elevated free homocysteine causes endothelial cell dysfunction and promotes early atherosclerosis and glomerulosclerosis. In this analytical study with a longitudinal follow-up, 29 children with first episode of nephrotic syndrome (FENS) aged 1–16 years along with 30 age andgender-matched healthy controls were enrolled. Plasma-free homocysteine was measured using high-performance liquid chromatography (HPLC). Other variables were measured using standard biochemical methods. The primary outcome measure was plasma-free homocysteine level in children with FENS and in controls. The secondary outcome measure was to observe the levels of plasma-free homocysteine in children with FENS at 12 weeks in remission and in steroid resistant states. Plasma-free homocysteine levels were significantly elevated in children with FENS at disease onset [Median (IQR) 2.170 (1.54–2.71); N = 29; P < 0.001], at 12 weeks of steroid-induced remission [Median (IQR) 1.946 (1.53–2.71); N = 22; P < 0.001], and in steroid-resistant states [Median (IQR) 2.262 (1.53–2.74); N = 7; P < 0.001] compared to controls. The levels did not decrease significantly at 12 weeks of steroid-induced remission compared to onset of nephrotic syndrome. Plasma-free homocysteine levels correlated positively with serum total cholesterol (P = 0.005; r = 0.362) and negatively with serum albumin (P = 0.032; r = 0.281). Plasma-free homocysteine levels are raised in children with FENS posing a risk of endothelial dysfunction which persists at least in short term. Long-term effects of raised plasma-free homocysteine needs to be studied.